Perancangan Sistem Informasi Geografis Pemetan Jalan Pada Dinas Pekerjaan Umum dan Penataan Ruang Kabupaten Lombok Tengah Menggunakan Metode Waterfall - Ihza dirgantara aji; Jihadul Akbar (Jurnal Publikasi Teknik Informatika, 2023)
The road is a means of land transportation that has a function to connect one area to another. Therefore the development of an area can run well if access and mobility are not disturbed or hindered. Road conditions are very important in facilitating the mobility of various sectors such as the economic, industrial, trade and transportation sectors. The Central Lombok PUPR Service has duties regulated in government regulation number 38 of 2007 regarding the division of government affairs between the provincial government and district/city regional governments. In accordance with regional regulation number 11 of 2016 concerning the formation and composition of the regional apparatus of the NTB province, the position of the public works and spatial planning office of the NTB province has the task of assisting the governor in carrying out regional government affairs in the field of public works and spatial planning geographic information system design for road mapping at the PUPR Service. make it easier for officers to check the road. It is hoped that this system can improve data management, so as to create quality road construction in the Central Lombok Regency area.